EVALUASI PRAKTIK KERJA INDUSTRI SEKOLAH MENENGAH KEJURUAN - Malik, Muh. Nasir; Hasanah, Hasanah (Universitas Negeri Makassar, 2015)
The research objective was to evaluate Â the readiness of the management of the implementation of vocational practice in the industry, Â The process of implementation, and Â factors constraints. Evaluative descriptive method CIPP models. The research sample are 12 public and private vocational taken proportionate stratified random sampling. The results showed: (1) evaluation of context is high, namely: (a) the quality of student competence, (b) the suitability of the implementation of the program with school policy, and (c) management readiness is high; (2) evaluation of input is very high, namely: (a) the readiness of student competence, (b) the readiness of the management of the school program, and (c) the readiness of teacher competence; (3) evaluation of the process, namely: (a) the process of implementation of the program running on schedule, but less relevant to the competencies required of students, (b) factors inhibiting factor, the lack of cooperation with the industry; and (4) evaluation of products is quite high, namely: (a) creating a link and match learning in schools, (b) increase student competence